Transformasi MIM Bolon menjadi MIM Digdaya Bolon: Langkah Strategis dalam Meningkatkan Kualitas Pendidikan - Khoir, Mulyanto Abdullah; Dewi, Rachma Rusdiana; Sayidah, Aminatus (Lembaga Yasin AlSys, 2025)
The transformation of MIM Bolon into MIM Digdaya Bolon is a strategic step to improve the quality of education at the basic level through comprehensive changes, not only in the name aspect, but also the curriculum, management and teaching methods. This article examines this transformation process using a qualitative approach and case studies to analyze the steps taken and their impact on the quality of education. This research found that the name change to